HUMANIZE : How People Centric Organizations Succeed in a Social World / Jamie Notter, Maddie Grant - Notter, Jamie
Knowing the tools of social media is a must for successful marketing these days, but the real promise of social media is the way it can teach us a whole new way of doing business. Humanize takes the principles underlying social media's growth and applies them to the way we lead and manage our organizations